Dynamic Fund Protection for Property Markets. Issue 3 (26th August 2022) - Siu, Tak Kuen; Nguyen, Ha; Wang, Ning
Abstract : This article aims to investigate, from an academic perspective, a potential application of dynamic fund protection to protect a mortgagor of a property against the downside risk due to falling property price. The valuation of the dynamic fund protection is discussed through modeling the property price and interest rate, which may be considered to be two key factors having a material impact on the mortgagor. Specifically, a mean-reverting process is used to describe the property price and the Heath-Jarrow-Morton theory is used to model the interest rate. The valuation is done via the use of a forward measure approach. The numerical solution to the pricing partial differential equation is obtained via applying the finite difference method. Numerical results with some model parameters being estimated from the data on an Australian residential property index and Australian zero-coupon yields and forward rates are provided. The implications of the numerical results for the potential implementation of the dynamic fund protection are discussed.